THE INFLUENCE OF SUPERVISORY ACTION ON JOB SATISFACTION OF ENTRY-LEVEL STAFF AT THE ACCOUNTING FIRMS IN BANDUNG CITY - Hadijah, Hady Siti (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2012)
Amount of client and also kind of industrial often result a work of audit have character is clerical andonly pursuing goals " Deadline". So that sometimes work of audit become something is routine. Workof audit which in have character the routine and clerical can weaken of supervision. This matterindication height turnover at the accounting firm.This research aim to know influence of supervisory actions to job satisfaction of entry-level staff, eithersimultaneously and also partially at the accounting firm in Bandung City. And for that used by thefollowing grand theory: for the variable of leadership and mentoring to job satisfaction, used theoryfrom Malayu ( 2003:189) and Robbin ( 1993:182). Variable of working conditions to jobsatisfaction, used theory from Luthan ( 1995:122) and Robbin ( 1993:181). While variable ofassignment to job satisfaction, used theory from Luthan ( 1995:121) and Robbin ( 1993:181).This research use the census method, with population counted 60 responder, that is entry-level stafffrom the accounting firm in Bandung City. Data required consisted of primary data obtained throughthe questioner and secondary data supporting this research. To analysis this research used by Analysisof Multiple Regression.The study find that three major element of supervisory actions recommended by the AECC, leadershipand mentoring, working conditions, and assignment, simultaneously have positive influence to jobsatisfaction of entry level staff equal to 47,20 %. Partially, influence element supervisory actions to jobsatisfaction of entry-level staff, leadership and mentoring have positive influence to job satisfaction ofentry-level staff equal to 19,70 %, working conditions have positive influence to job satisfaction equalto 32,50 %, and assignment have positive influence to job satisfaction equal to 15,20 %.